(untitled) (Journal of Engineering, 2014)
After studying the reality of application to occupational safety in new Iraqi building projects and sampling the situation wilt that in developed and neighboring countries, researcher found that there is a big gap in the level of safety application conditions, this indicates the need fora quick and clear reference for local engineers to use it on site for safety conditions in their projects . As a case study the monitors work the researcher studied a huge project in the United Arab Emirates.This project considered for safety requirements to highest grades. This case study may be far away from the projects in Iraq, but we hope to rise the Iraqi work level in the near future. After seeing the way of administration work and how they were rated the severity of each phase of the work, an idea was builtabout the most dangerous situations in projects with multiple floorsbuildings. To find multiple solutions to the risk, researchers identified 46 cases with their ratings, type of perceived risk in each case, and displayed a format survey to the most important specialized institutions and companies operating in Iraq and the United Arab Emirates. Finally theresearcher takes the results,and format a software that any user can use in his personal computer to studythe expected risk,how to avoid it and how to deal with it if it happens.